TENDINȚE GEOPOLITICE ÎN BAZINUL MĂRII NEGRE ÎN CONTEXTUL RĂZBOIULUI DIN UCRAINA - Cebotari, Svetlana (CEP USM, 2024)
The Black Sea region in the context of the actual geopolitic evolutions The Black Sea region over the centuries played an important geostrategic role in the relations between the great powers. Currently, at the confluence of two Versailles culture and religions, the Christian and Islamic and many nations, the Black Sea is a space of both convergence and collision of the interests of the riparian countries, but also of the various international actors. This article outlines the main interests of the great powers. The objective of this article is to highlight the main geopolitical trends taking place in the Black Sea basin, trends that are conditioned by the emergence of the war in Ukraine
CEBOTARI, Svetlana. Tendințe geopolitice în bazinul Mării Negre în contextul războiului din Ucraina. In: Strengthening Security and Stability in the New National, Regional and Global Realities: conferinţa ştiinţifică internaţională. Chişinău: CEP USM, 2024, pp. 70-79.
Keywords: război ruso-ucrainean; Black Sea basin; Bazinul Mării Negre